3D CFD simulations of acetone hydrogenation in randomly packed beds for an isopropanol–acetone–hydrogen chemical heat pump. (5th February 2016) - Peng, Wenping; Xu, Min; Huai, Xiulan; Liu, Zhigang
Highlights: 3D CFD simulations on acetone hydrogenation are achieved in randomly packed-bed reactors. Heat and mass transfer characteristics are compared at intra-particles and in fluid zone of the bed. Influences of structure parameters are evaluated on acetone productivity and isopropranol selectivity. Abstract: Isopropanol–acetone–hydrogen chemical heat pump (IAH-CHP) is a system having the ability to improve energy-grade and to achieve energy storage simultaneously. Acetone hydrogenation is an important part of IAH-CHP and directly affects the performance of IAH-CHP. In this work, the fully three-dimensional simulations on acetone hydrogenation in randomly packed-bed reactors with small tube-to-particle diameter ratio D / d p were carried out by Computational Fluid Dynamics (CFD). The study focused on the heat and mass transfer characteristics at inter- and intra-particles of the bed. The results indicate that the resistance of mass transfer at intra-particles is maximum in the entire transport process. Particle-to-fluid heat transfer is the main resistance of heat transfer in the bed. In addition, the synergy between transport of components and reaction rate at intra-particles was analyzed for various structural parameters, such as porosity εp, pore diameter d o, particle diameter d p and tube-to-particle diameter ratio D / d p, in order to improve the utilization efficiency of catalyst. This study provides a detailed understanding on transport characteristics both at intra-particles and in fluid zone in randomly packed-bed reactors with small D / d p, providing a guideline for catalyst and reactor design for this type of chemical heat pump.